Complex control of the ecological state of the components of the environment and biota of the eastern part of the Avachinsky Gulf - Yu.A., Galysheva; A.D., Pelekh; T.V, Boychenko; V.E., Metreveli (Edelweiss Applied Science and Technology, 2025)
The purpose of this work is to conduct a comprehensive assessment of the ecological status of the eastern part of Avachinsky Gulf. This assessment is based on the results of monitoring chemical and microbiological parameters of the aquatic environment and sediments, as well as biotesting the toxicity of the environment and evaluating the abundance of macrobenthos. The conditions of anthropogenic transformation of the natural ecological and chemical background are primarily observed in the inner part of the bay (Avacha Bay). Conversely, the natural climatic and oceanological processes are predominant in the open area of Khalaktyrsky Beach (the open part of the gulf). Significant differences were identified in the content of phosphorus compounds (Pmin), ammonium ions (NH4+), the total number of heterotrophic microorganisms, and sanitary-indicative groups of bacteria. According to biotesting results, a toxic effect was detected in the gulf environment. Despite the presence of environmental risk factors in Avacha Bay, oxygen indicators suggest a good water exchange between the bay and the open waters of the gulf, indicating a relatively strong mechanism for maintaining the stability of this water area. Additionally, the abundance of macrobenthos in the study area currently remains within normal levels, reflecting a balanced ecological condition.